Advances in the eradication of foot-and-mouth disease in South America: 2011–2020 - Rivera, Alejandro Mauricio; Sanchez-Vazquez, Manuel Jose; Pituco, Edviges Maristela; Buzanovsky, Lia Puppim; Martini, Monica; Cosivi, Ottorino (Frontiers in Veterinary Science, 2023)
For more than 70 years, the countries of South America have been attempting to eliminate foot-and-14 mouth disease (FMD), but a regional strategy had not been established by all the affected countries 15 until 1988. The Action Plan 1988–2009 of the Hemispheric Program for the Eradication of Foot-and-16 Mouth Disease (PHEFA 1988–2009) resulted in an FMD-free status in 88.4% of the bovine 17 population of South America. However, countries of the Andean subregion maintained an FMD 18 endemic. In addition, sporadic outbreaks in vaccinated cattle populations have been reported in 19 countries of the Southern Cone, endangering the disease-free status in these countries. Within this 20 context, the PHEFA 2011–2020 was approved to eliminate FMD from the subcontinent, and this 21 review describes the most important milestones during its execution. FMD in Ecuador and sporadic 22 outbreaks in the Southern Cone subregion were effectively eliminated. The outbreaks that occurred in 23 Colombia in 2017 and 2018 were successfully controlled. The type C virus was removed from the 24 vaccines in use in most countries, based on a risk assessment. This review also describes the progress 25 made by the countries advancing towards official recognition as FMD-free in all their territories, with 26 Bolivia, Brazil, and Peru leading the progressive suspension of vaccination to achieve FMD-free 27 status without vaccination. Consequently, at the end of PHEFA 2011–2020, Venezuela was, and still 28 is, the only country in the region whose control program has suffered setbacks, and no evidence has 29 suggested that the transmission and infection of the bovine population have been eliminated. At the 30 end of 2020, a new PHEFA Action Plan 2021–2025 was approved with a five-year horizon, to 31 complete the eradication of the disease in the Americas.